Multilayer specially-infiltrated MOF (Metal Organic Framework) derived composite membrane as well as preparation method and dual-function application thereof

By using multi-scale deposition and thermal conversion methods to form a multi-layer structure on the MOF base film, the problem of difficulty in achieving oil-water separation and catalytic degradation at the same time is solved, and efficient oil-water separation and catalytic degradation performance is achieved, and the performance of oil-water separation and catalytic degradation is improved. Material stability and catalytic efficiency.

CN119455706AActive Publication Date: 2025-02-18HANGZHOU LUHONG TECHNOLOGY CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411589333.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-08
Publication Date
2025-02-18
Estimated Expiration
2044-11-08

AI Technical Summary

Technical Problem

When treating oil-containing wastewater, it is difficult to achieve oil-water separation and catalytic degradation of water-soluble organic pollutants at the same time. During the preparation process, there is coordination of MOF layer thickness and continuity, compatibility, catalyst dispersion and multi-level structure control. etc.

Method used

Multi-scale deposition and thermal conversion method are used to form multi-layer structures on the surface and pores of MOF base film. A dense and continuous MOF film is grown by in-situ growth method, and nanometal oxide clusters are calcined at high temperature to form, producing steep surface energy. Gradient, achieving hydrophilic but impermeable properties.

Benefits of technology

The dual functional performance of oil-water separation and photofenton degradation of water-soluble organic pollutants is achieved, which improves the catalytic performance and separation efficiency. The surface of the material increases the contact time and area between pollutants and catalytic sites, and has excellent solvent resistance chemical stability. sex.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005125149310000041
    Figure BDA0005125149310000041
  • Figure HDA0005125149320000011
    Figure HDA0005125149320000011
  • Figure HDA0005125149320000012
    Figure HDA0005125149320000012
Patent Text Reader

Abstract

The invention discloses a multi-layer special infiltrated MOF (Metal Organic Framework) derivative composite membrane as well as a preparation method and dual-function application thereof.The preparation method comprises the following steps: forming a compact and continuous MOF membrane on an inorganic substrate by adopting an in-situ growth method, and introducing metal activity on the surface of the MOF membrane and in a pore channel by adopting vapor deposition and heat treatment means, so as to obtain the multi-layer special infiltrated MOF derivative composite membrane. The multi-layer hydrophilic directional permeation multifunctional surface composite metal film material consisting of hydrophilic active bulges and a super-hydrophobic separation layer is formed; the material is simple and practical in preparation method, has a dual-function application value, can realize oil-water separation and catalytic degradation of soluble organic pollutants, and has a good application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of multifunctional composite membrane materials, and in particular to a multilayer special infiltration MOF-derived composite membrane and a preparation method thereof, as well as applications in oil-water separation and photo-Fenton degradation of water-soluble organic pollutants. Background Art

[0002] With the continuous development of industrialization and the rapid growth of population, water resources are deteriorating. Human beings are facing the crisis of water shortage, and environmental governance is urgent. Among them, the pollution of oily wastewater has also had a serious impact on the ecological environment. From the perspective of green chemistry, if the oil or macromolecules in the water can be recycled, the recycling rate of raw materials can be greatly improved. The introduction of catalytic membranes provides a feasible idea for the above research.

[0003] In recent years, the use of catalytic membranes for oil-water separation and catalytic degradation of pollutants in water has become a new development field and research direction in water treatment. In the field of catalysis, metal organic frameworks (MOFs) are porous framework materials whose pores can be used to load metal nanoparticles (MNPs), which have a strong advantage in improving catalytic performance. As the research on MOFs continues to deepen, scholars have integrated them into membrane structures, which can not only overcome the inherent fragility and rigidity in practical applications, but also serve as a promising alternative method, gaining greater attention in the field of molecular sieving, and the technology of growing MOFs on different porous supports has made significant progress. In the field of oil-water separation, MOFs can use the hydrophobicity of their structure or organic groups on the ligands to separate oil-water mixtures, but there are very few literature reports on catalytic membrane reaction devices that use the special structure of MOFs to separate oil-water mixtures and catalytically degrade organic molecules to remove pollutants, integrating catalysis and separation.

[0004] Since MOF catalytic membranes have large surface areas and uniform pores, they have great advantages in the fields of catalysis and efficient separation. Although great progress has been made in the research of catalytic membranes, there are still many problems in the preparation process, such as the coordination of MOF layer thickness and continuity, the compatibility between MOF layer and substrate, the dispersion of catalysts, and the multi-level structure of catalytic membranes cannot be accurately and effectively controlled.

[0005] Therefore, it is particularly important to design a composite catalytic membrane material with good stability that can not only separate oil-water mixtures but also catalytically degrade water-soluble pollutants in the same unit when treating oily wastewater. Summary of the invention

[0006] The present invention aims to provide a multi-layer special infiltration MOF-derived composite membrane and its preparation method and dual-functional application. In the preparation process of the composite membrane material, the organic metal diffuses on the surface or inside of the MOF base through multi-scale deposition and thermal conversion to generate a steep energy gradient, thereby forming a multi-level hydrophilic directional permeation dual-functional surface composed of hydrophilic active protrusions and super-hydrophobic separation layers.

[0007] The technical solution of the present invention is as follows:

[0008] A method for preparing a multilayer special infiltration MOF-derived composite membrane comprises the following steps:

[0009] (1) Using in situ growth method to grow dense and continuous MOF membrane on inorganic skeleton;

[0010] The inorganic skeleton can be a metal mesh, such as a copper mesh, a nickel mesh, a foam copper, a foam nickel, etc., with a specification of 100 to 400 meshes; preferably a copper mesh;

[0011] MOF can be Cu-BTC, Cu-BDC or NH2-UiO-66, preferably Cu-BTC; the in-situ growth method of Cu-BTC film is as follows: a copper mesh is vertically placed in an ethanol solution containing copper nitrate trihydrate and trimesic acid, and hydrothermally reacted at 80°C for 12 hours to obtain a copper mesh with a Cu-BTC film; preferably, the molar ratio of copper nitrate trihydrate to trimesic acid is 1:1;

[0012] (2) placing the inorganic skeleton with the MOF film grown thereon obtained in step (1) and the metal precursor into a reaction kettle, performing a vapor deposition reaction at 80 to 150° C. (preferably 110° C.) for 2 h, and then cooling to room temperature to obtain a nano-metal particle-MOF film;

[0013] The metal precursor is an organic metal salt, such as an organic iron salt, an organic nickel salt, an organic cobalt salt, etc.; preferably an organic iron salt, particularly preferably ferrocene;

[0014] The metal precursor has a loading amount of 1 to 20% of the mass of the MOF film based on the metal contained, preferably 5%;

[0015] (3) calcining the nano-metal particle-MOF film obtained in step (2) at 150-220° C. (preferably 180° C.) for 2-6 h (preferably 2 h) to obtain the multi-layer special infiltration MOF-derived composite film.

[0016] The invention relates to a multi-layer special infiltration MOF-derived composite membrane prepared by the preparation method.

[0017] The multi-layer special infiltration MOF-derived composite membrane described in the present invention can be used for oil-water separation and photo-Fenton degradation of water-soluble organic pollutants.

[0018] Compared with the prior art, the present invention has the following advantages:

[0019] (1) The present invention provides a method for preparing a multi-layer special infiltration MOF-derived composite membrane, wherein easily sublimable metal organic molecules are connected to the functional groups on the surface and pores of the MOF-based membrane by a multi-scale CVD vapor deposition method. Finally, after thermal conversion, the metal organic molecules on the membrane surface are calcined into nano-metal oxide clusters, while the metal organic molecules loaded in the pores that are not completely calcined are converted into a form connected to organic functional groups and exist in the membrane fault structure, generating a steep surface energy gradient, making the surface hydrophilic but impermeable to water and permeable to oil.

[0020] (2) The present invention provides a multilayer special infiltration MOF-derived composite membrane that exhibits superior dual functionality in treating aqueous organic oily wastewater, while achieving oil-water separation and photo-Fenton degradation of water-soluble organic pollutants.

[0021] (3) Compared with the traditional super-hydrophobic surface, the bifunctional composite membrane material prepared by the present invention is beneficial to increase the contact time and area between pollutants and catalytic sites, and also has excellent solvent resistance and chemical stability, is simple to prepare, easy to operate, and pollution-free. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 : SEM image of multilayer special infiltration MOF-derived composite membrane in Example 1; a-surface structure, b-cross-section structure.

[0023] Figure 2 : TEM image of multilayer special infiltration MOF-derived composite membrane in Example 1. DETAILED DESCRIPTION

[0024] The technical scheme of the present invention is clearly and completely described below in conjunction with specific embodiments, but the following described embodiments are some embodiments of the present invention, rather than all embodiments, and are only used to illustrate the present invention, and should not be regarded as limiting the scope of the present invention. If specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0025] Embodiment 1:

[0026] Preparation of FcCT@CC membrane:

[0027] Take a brass mesh (2 cm × 3 cm) with a brass-colored, unoxidized surface, and ultrasonically clean the mesh in hydrochloric acid and ethanol, respectively, and dry it in the air. Fix the cleaned mesh vertically on a bracket (to support the mesh).

[0028] Weigh 0.362g (1.5mmol) of copper nitrate trihydrate and 0.315g (1.5mmol) of trimesic acid, dissolve in 16ml of ethanol, sonicate until all solids are dissolved, vertically place the copper mesh fixed on the bracket in the ethanol solution containing copper nitrate trihydrate and trimesic acid, and place it in an oven for hydrothermal reaction at 80℃ for 12h. After the reaction is completed, take out the hydrothermal kettle, place it on the laboratory table and cool it naturally to room temperature, take out the copper mesh with Cu-BTC with clean tweezers, repeatedly wash it in ethanol to remove excess copper nitrate and trimesic acid on the surface, and place it in an oven for vacuum drying to obtain a Cu-BTC film.

[0029] 0.093 g (0.5 mmol) of ferrocene was weighed and placed in a 25 mL hydrothermal reactor. The dried Cu-BTC membrane was fixed on a bracket and placed vertically in the reactor containing ferrocene. It was placed at 110 °C for 2 h in gas phase loading. After the reaction was completed, it was cooled to room temperature and taken out. It was then calcined at 180 °C for 2 h to obtain the FcCT@CC membrane.

[0030] Embodiment 2:

[0031] Preparation of FcCD@CC membrane:

[0032] The difference from Example 1 is that in the preparation of the Cu-BDC film, the solvent and the ligand are replaced by N,N-dimethylformamide and terephthalic acid.

[0033] Embodiment 3:

[0034] Preparation of FcNU@CC membrane:

[0035] The difference from Example 1 is that the NH2-UiO-66 film is prepared by in-situ growth;

[0036] Embodiment 4:

[0037] Preparation of FcCT@C-CF membrane:

[0038] The difference from Example 1 is that the copper mesh is replaced with foam copper.

[0039] Embodiment 5:

[0040] Preparation of FcCT@CN membrane:

[0041] The difference from Example 1 is that the copper mesh is replaced by a nickel mesh.

[0042] Embodiment 6:

[0043] Preparation of FcCT@C-NF membrane:

[0044] The difference from Example 1 is that the copper mesh is replaced with nickel foam.

[0045] Embodiment 7:

[0046] Preparation of 0.5FcCT@CC membrane:

[0047] The difference from Example 1 is that 0.047 g (0.25 mmol) of ferrocene is used to participate in the reaction.

[0048] Embodiment 8:

[0049] Preparation of 2FcCT@CC membrane:

[0050] The difference from Example 1 is that 0.1867 g (1 mmol) of ferrocene is used to participate in the reaction.

[0051] Embodiment 9:

[0052] Preparation of FcCT@CC-150 membrane:

[0053] The difference from Example 1 is that the Fe / Cu-BTC film is calcined at 150°C.

[0054] Embodiment 10:

[0055] Preparation of FcCT@CC-200 membrane:

[0056] The difference from Example 1 is that the Fe / Cu-BTC film is calcined at 200°C.

[0057] Embodiment 11:

[0058] Preparation of CoCT@CC membrane:

[0059] The difference from Example 1 is that 0.093 g (0.5 mmol) of ferrocene is replaced by 0.095 g (0.5 mmol) of cobaltocene.

[0060] Embodiment 12:

[0061] Preparation of NiCT@CC membrane:

[0062] The difference from Example 1 is that 0.093 g (0.5 mmol) of ferrocene is replaced by 0.094 g (0.5 mmol) of nickelocene.

[0063] Comparative Example 1:

[0064] Preparation of Cu-BTC film:

[0065] The difference from Example 1 is that the prepared Cu-BTC membrane is calcined at 180° C. for 2 h to obtain the Cu-BTC membrane.

[0066] Comparative Example 2:

[0067] Preparation of Fe / Cu-BTC membrane:

[0068] The difference from Example 1 is that the prepared Fe / Cu-BTC film is no longer subjected to heat treatment.

[0069] The composite membranes prepared in Examples 1-12 and the composite membranes prepared in Comparative Examples 1-2 were subjected to separation catalytic tests. First, the membrane was fixed horizontally in a container, and a mixture of 300 mL of dye wastewater containing 50 mg / L X-3B and 0.5 mL / L hydrogen peroxide and 300 mL of dichloromethane was poured on the upper layer of the membrane. The separation time was 30 min, and then the oil passed through the composite membrane layer by its own gravity. The flux of the oil was recorded, and the ultraviolet lamp was turned on. After catalytic degradation for 1 hour, its absorbance was measured.

[0070] The final membrane separation efficiency for oil and water is calculated by the following formula:

[0071] DE=D1 / D0×100% (1)

[0072] D0 is the theoretical quantity under single-phase conditions, and D1 is the permeate flux.

[0073] The catalytic degradation efficiency of the membrane is calculated by the following formula:

[0074] SE = (A0 - A1) / A0 × 100% (2)

[0075] A0 is the absorbance of the original solution, and A1 is the absorbance of the permeate at 535 nm.

[0076] The oil-water separation efficiency and photo-Fenton catalytic degradation efficiency were calculated, and the results are shown in Table 1.

[0077] Table 1 Comparison of the performance of the prepared bifunctional metal organic framework catalytic membranes

[0078]

Claims

1. A method for preparing a multilayer special infiltration MOF-derived composite membrane, characterized in that: The following steps are involved: (1) Using in situ growth method to grow dense and continuous MOF membrane on inorganic skeleton; The inorganic framework uses a metal mesh; MOF is Cu-BTC, Cu-BDC or NH2-UiO-66; (2) placing the inorganic skeleton with the MOF film grown thereon obtained in step (1) and the metal precursor into a reaction kettle, performing a vapor deposition reaction at 80 to 150° C. for 2 h, and then cooling to room temperature to obtain a nano-metal particle-MOF film; The metal precursor is selected from an organic iron salt, an organic nickel salt or an organic cobalt salt; (3) The nano-metal particle-MOF film obtained in step (2) is calcined at 150-220° C. for 2-6 hours to obtain the multi-layer special infiltration MOF-derived composite film.

2. The method for preparing a multilayer special infiltration MOF-derived composite membrane according to claim 1, characterized in that: In step (1), the inorganic framework is made of copper mesh, nickel mesh, foam copper or foam nickel, with a specification of 100 mesh to 400 mesh.

3. The method for preparing a multilayer special infiltration MOF-derived composite membrane according to claim 1, characterized in that: In step (1), the MOF is Cu-BTC; the in-situ growth method of the Cu-BTC film is as follows: a copper mesh is vertically placed in an ethanol solution containing copper nitrate trihydrate and trimesic acid, and subjected to a hydrothermal reaction at 80° C. for 12 hours to obtain a copper mesh with a Cu-BTC film grown thereon; wherein the molar ratio of copper nitrate trihydrate to trimesic acid is 1:

1.

4. The method for preparing a multilayer special infiltration MOF-derived composite membrane according to claim 1, characterized in that: In step (2), the metal precursor is ferrocene.

5. The method for preparing a multi-layer special infiltration MOF-derived composite membrane according to claim 1, characterized in that: In step (2), the loading amount of the metal precursor based on the contained metal is 1 to 20% of the mass of the MOF film.

6. The method for preparing a multilayer special infiltration MOF-derived composite membrane according to claim 1, characterized in that: In step (3), the calcination temperature is 180° C. and the calcination time is 2 h.

7. A multi-layer special infiltration MOF-derived composite membrane prepared by the preparation method according to any one of claims 1 to 6.

8. Application of the multilayer special infiltration MOF-derived composite membrane as claimed in claim 7 in oil-water separation and photo-Fenton degradation of water-soluble organic pollutants.

Citation Information

Patent Citations

  • Preparation method of ferrocene-modified Fenton catalyst for iron-based metal-organic framework material

    CN107519934A

  • Microphone-shaped MOFs-based oil-water separation metal net film and preparation method thereof

    CN110180218A

  • Modified foamy copper material as well as preparation method and application thereof

    CN111019148A

  • Super-hydrophilic foamy copper separation membrane based on two-dimensional MOF structure, super-hydrophobic foamy copper separation membrane based on two-dimensional MOF structure, preparation method and application

    CN116966757A

  • Preparation method and application of self-repairing MOFs catalytic membrane

    CN118356979A